BEST EMPLOYEE ASSESSMENT DECISION SUPPORT SYSTEM USING WEIGHTED PRODUCT METHOD BASED ON MOBILE WEB AT PUTRI COLECTION STORE - Nungsiyati, Nungsiyati; Nurbaiti, Putri; Suyono, Suyono; Fitrian, Yuri (Jurnal TAM (Technology Acceptance Model), 2023)
The decision support system is a computer-based system that can be designed to assist in the decision-making process regarding the results of selecting the best employees at the Putri Collection Store sales business . In selecting the best employees, we use the Weighted Product method, which is a method used to find optimal alternatives from a number of alternatives with a certain number of criteria through weighted multiplication of the performance rating of each alternative on each attribute. In selecting the best employees at the Putri Collection Store, five criteria are used, namely Discipline, Discipline, Responsibility, Attendance, Cooperation. The results of this research, the Weighted Product Method, make it possible to assign relative weights or values to each employee assessment criterion. By using Weighted Products, stores can easily adjust criteria weights according to specific interests and needs. This allows flexibility in adjusting the determination of the best employees according to the objectives of the business location. This method makes it possible to make decisions based on robust data analysis. By giving weight to each criterion, you can measure employee performance objectively and based on data, reducing the potential for subjective bias. By combining the Weighted Product Method and a mobile web-based platform, you can optimize the process of determining the best employees, increase accuracy, and respond quickly to changes in the organization.